Oxidation of Ru(III)‐Bound Thiocyanate with Peroxomonosulfate: Kinetic and Mechanistic Studies. Issue 3 (29th December 2015) - Sarkar, Papiya; Chatterjee, Debabrata
ABSTRACT: The reaction of [Ru III (edta)(SCN)] 2− (edta 4− = ethylenediaminetetraacetate; SCN − = thiocyanate ion) with the peroxomonosulfate ion (HSO5 − ) has been studied by using stopped‐flow and rapid scan spectrophotometry as a function of [Ru III (edta)], [HSO5 − ], and temperature (15–30ºC) at constant pH 6.2 (phosphate buffer). Spectral analyses and kinetic data are suggestive of a pathway in which HSO5 − effects the oxidation of the coordinated SCN − by its direct attack at the S‐atom (of SCN − ) coordinated to the Ru III (edta). The high negative value of entropy of activation (Δ S ≠ = −90 ± 6 J mol −1 deg −1 ) is consistent with the values reported for the oxygen atom transfer process involving heterolytic cleavage of the O‐O bond in HSO5 − . Formation of SO4 2−, SO3 2−, and OCN − was identified as oxidation products in ESI‐MS experiments. A detailed mechanism in agreement with the spectral and kinetic data is presented.